By two: A two-dimensional mobile game model for novice developers - Abdallah Qusef; Abdallah Ayasreh; Adnan Shaout; Muhanna Muhanna (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The objective of this research was to discuss the processes and challenges encountered in the creation of mobile games for both Android and iOS platforms, which would help the novice game developers to enter the big world of mobile game industry. We highlighted each phase of the mobile game development. These involved suggestions on efficient brainstorming of ideas, proper selection of game engine, game design, number and type of pages, creation of levels, and distribution of complexity across the game level. In addition, other factors were considered such as the creation of User Interface and User Experience (UI/UX) as well as definition of the screen object’s sizes and positions that would be suitable in all mobile devices. The importance of agile cycles of alpha and beta testing was also discussed, particularly its influence on the enhancement of game features. However, a successful game is recognized based on its earnings. Hence, a guide on how to properly market the game was also included. A model game called “By Two” was used in this study to illustrate and explain the steps in detail.